The Crime of Corpse Theft in Cemeteries in the Perspective of Islamic Criminal Law - Septi Angraini Harahap; Sukiati (Journal Equity of Law and Governance, 2024)
The theft of corpses in Indonesian cemeteries, often for black magic and rituals, is a growing concern. The Criminal Code (KUHP) penalizes this act with up to one year and four months in prison and a fine of 4,500 rupiahs under Article 180. The Draft Criminal Code proposes harsher penalties, including up to two years in prison and a higher fine, under Article 271. This study examines corpse theft from the perspective of Islamic criminal law and assesses the relevance of current KUHP sanctions. The findings reveal that Islamic law strictly prohibits corpse theft, categorizing it as a serious violation of human dignity and a jarimah hudud crime for sariqah, rather than jarimah ta'zir. However, ta'zir sanctions apply if the conditions for hudud are unmet. This research aims to contribute to the discourse on the various forms of theft in society, emphasizing the importance of context and the evolving nature of legal issues in Islamic criminal law.